Sistem Laporan Keuangan Berbasis Aplikasi Website Pada Toko Maestro Jaya - Suwarno liang; Jon Susanto (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
Rapid technological advances greatly help daily activity, so many people start using technology in their business. Maestro Jaya shop is one of the MSMEs located in Batam City, the shop owner has problems in producing financial reports either monthly or annually. So in this article, the author implements a system that supports daily activities at the store such as making invoices, payments, and journaling to get financial reports. The author uses the PHP programming language and waterfall as the development method. The final result of this research is a website application that has been used by the shop owner for the shop's daily activities.